Optical spectroscopy and photometry of main-belt asteroids with a high orbital inclination. (February 2017) - Iwai, Aya; Itoh, Yoichi; Terai, Tsuyoshi; Gupta, Ranjan; Sen, Asoke; Takahashi, Jun
Abstract: We carried out low-resolution optical spectroscopy of 51 main-belt asteroids, most of which have highly-inclined orbits. They are selected from D-type candidates in the SDSS-MOC 4 catalog. Using the University of Hawaii 2.2 m telescope and the Inter-University Centre for Astronomy and Astrophysics 2 m telescope in India, we determined the spectral types of 38 asteroids. Among them, eight asteroids were classified as D-type asteroids. Fractions of D-type asteroids are 3.0 ± 1.1 for low orbital inclination main-belt asteroids and 7.3 ± 2.0 for high orbital inclination main-belt asteroids. The results of our study indicate that some D-type asteroids were formed within the ecliptic region between the main belt and Jupiter, and were then perturbed by Jupiter.